Annual Plan 1972-73 Part II-Statements Government of Maharashtra - Planning Commission (Planning Commission, 1972)
List of Schemes included in the state Plan Abstract Statement showing outlays included in the Annual Plan 1972-73 Head of Development : Agricultural Programme/Agricultural Production including land Development Statement Showing Outlay Included in the Annual Plan 1972-73 Central Sponsored (Central Plan) Annual Plan 1972-73 Targets and achievements for selected programmes.
Finance Department (Planning) Government of Maharashtra